ภาวะผู้นำเต็มรูปแบบ: ปัจจัยสำคัญในการบริหารโรงเรียนประชารัฐ - เปียถนอม ปทุมพร (Journal of Education Studies, Chulalongkorn University, 2018)
Abstract In order to develop the country under the concept of Thailand 4.0, public-private collaboration is set as a tool for steering the development by focusing on collaboration among several sectors. This will be done through a memorandum of understanding, activities and research. The Pracharath School is one of the projects created in the context of Thailand 4.0 under the System Theory, that is, the combination of the school management mechanisms of the government and the private sector (input) under the new collaboration (process) that is driven by coaching organizations (private sector), and this should lead to greater academic achievement (output). Managing Pracharath School under the concept of full range leadership is an idea that combines the transactional leadership concept consisting of Laissez-Faire, Management-by Exception and Contingent Rewards, and the transformational leadership concept consisting of Individual Consideration, Intellectual Stimulation, Inspirational Motivation and Idealized Influence. Full range leadership is used as the a paradigm to change the circumstances of the previous administration of the basic educational schools that includes some leaders with certain leadership styles, including the laissez-faire leadership (LF), the management-by-exception (MBE) and the contingent reward (CR). These caused the overall picture of Thailand’s academic achievements worsen. Therefore, if the structure and the process of educational administration were not changed, such problems would continue to remain. If the policy of managing Pracharath School should be adopted along with the concept of full range leadership, this could bring about further integrated solutions.